Electroplating and magnetostructural characterization of multisegmented Co54Ni46/Co85Ni15 nanowires from single electrochemical bath in anodic alumina templates - Prida, Víctor M.; García, Javier; Iglesias, Lucia; Vega, Víctor; Görlitz, Detlef; Nielsch, Kornelius; Barriga Castro, Enrique Díaz; Mendoza Reséndez, Raquel; Ponce, Arturo; Luna Criado, Carlos (Springer, 2013)
Highly hexagonally ordered hard anodic aluminum oxide membranes, which have been modified by a thin cover layer of SiO2 deposited by atomic layer deposition method, were used as templates for the synthesis of electrodeposited magnetic Co-Ni nanowire arrays having diameters of around 180 to 200 nm and made of tens of segments with alternating compositions of Co54Ni46 and Co85Ni15. Each Co-Ni single segment has a mean length of around 290 nm for the Co54Ni46 alloy, whereas the length of the Co85Ni15 segments was around 430 nm. The composition and crystalline structure of each Co-Ni nanowire segment were determined by transmission electron microscopy and selected area electron diffraction techniques. The employed single-bath electrochemical nanowire growth method allows for tuning both the composition and crystalline structure of each individual Co-Ni segment. The room temperature magnetic behavior of the multisegmented Co-Ni nanowire arrays is also studied and correlated with their structural and morphological properties.